A new Christian identity : Christian Science origins and experience in American culture - Voorhees, Amy B. (The University of North Carolina Press, 2021)
"In this study of Christian Science and the culture in which it arose, Amy B. Voorhees emphasizes Mary Baker Eddy's foundational religious text, Science and Health with Key to the Scriptures, rather than Eddy's already well known biography. Introducing the experiences of everyday adherents from the earliest days of Science and Health's appearance in 1875, Voorhees shows how Christian Science came into dialogue with more mainstream Christian theologies of healing and health. Viewing the material world as illusory and sickness as a state that can be corrected by prayer, Christian Science emerged as an anti-mesmeric, millennialist form of Christianity that interpreted the Bible and approached emerging modern medicine on its own terms"--